The Influence of Budget Participation and Organizational Commitment to the Performance of Regional Government Apparatus - Anggadini, Sri Dewi; Wulansari, Lupi; Damayanti, Sari (International Journal of Management Science and Information Technology, 2021)
This study aims to determine how much influence of Budget Participation and Organizational Commitment on the Performance of Local Government Apparatus at the Bandung City Government Financial and Asset Management Agency. The method used in this research is descriptive method and verification method with a quantitative approach. The analytical tools used are Multiple Linear Regression, Correlation Analysis Test, Determination Analysis Test, and Partial Hypothesis Test (t test). The sampling technique used is nonprobability sampling technique. The population in this study were employees of the Bandung City Government Financial and Asset Management Agency (BPKA). The number of samples in this study amounted to 30 employees consisting of the Budget Division, the Treasury Division and the Accounting Division. While the method of analysis used in this study is multiple linear regression. The program used in analyzing the data used the Statistical Package for Social Sciences (SPSS) ver.23. Based on the research results, it shows that there is a significant and positive influence between budget participation and the performance of local government officials and organizational commitment has a significant and positive effect on the performance of local government officials.